Finding Adapted Quinones for Harvesting Electrons from Photosynthetic Algae Suspensions. Issue 15 (16th August 2021) - Sayegh, Adnan; Perego, Luca A.; Arderiu Romero, Marc; Escudero, Louis; Delacotte, Jérôme; Guille‐Collignon, Manon; Grimaud, Laurence; Bailleul, Benjamin; Lemaître, Frédéric
Abstract: Among all the chemical and biotechnological strategies implemented to extract energy from oxygenic photosynthesis, several concern the use of intact photosynthetic organisms (algae, cyanobacteria…). This means rerouting (fully or partially) the electron flow from the photosynthetic chain to an outer collecting electrode thus generating a photocurrent. While diverting photosynthetic electrons from living biological systems is an encouraging approach, this strategy is limited by the need to use an electron shuttle. Redox mediators that are able to interact with an embedded photosynthetic chain are rather scarce. In this respect, exogenous quinones are the most frequently used. Unfortunately, some of them also act as poisoning agents within relatively long timeframes. It thus raises the question of the best quinone. In this work, we use a previously reported electrochemical device to analyze the performance of different quinones. Photocurrents (maximum photocurrent, stability) were measured from suspensions of Chlamydomonas reinhardtii algae/quinones by chronoamperometry and compared to parameters like quinone redox potentials or cytotoxic concentration. From these results, several quinones were synthesized and analyzed in order to find the best compromise between bioelectricity production and toxicity. Abstract : Performances of different quinones as redox mediators are investigated from suspensions of photosynthetic microalgae to produce photocurrents by using a miniaturized well‐type Au/ITO electrochemical device. Some electrochemical aspects are considered (maximum photocurrent, stability) but side‐effects of quinones are also studied (cytotoxic concentration, ATPsynthase). Correlations with redox potentials give a first view to find the best compromise between bioelectricity production and toxicity.